การผ่าตัดรักษา Cavernous Carotid Artery Aneurysms Surgical Treatment of Cavernous Carotid Artery Aneurysms - ศรีอมรรัตนกุล กิติพร; อัครธรรมโชติ นาแสง; วงศ์สุริยนันท์ สมเกียรติ (Thai Journal of Neurological Surgery, 2025)
Cavernous carotid artery aneurysm is the aneurysm located at cavernous segment of internal carotid artery (ICA). In the past, the main surgery was direct clipping which caused significant cranial nerve deficits and morbidities due to the cavernous sinus exposure, therefore the indirect treatment was developed and almost totally replaced the former treatment. The principle of indirect treatment is parent artery occlusion with or without extracranial-intracranial (EC-IC) bypass. Several procedures for the parent artery occlusion include trapping of aneurysm, proximal occlusion of ICA, and proximal occlusion of common carotid artery. The best procedure is still controversial. Also, the necessity (with or without bypass) and the type (low-flow or high-flow type) of EC-IC bypass is debatable. The data of many literatures were collected and reviewed in this article about the treatment methods and outcomes. From many information, we can conclude that the most appropriate treatment is high-flow bypass with cervical ICA ligation except for the CCAA presented with direct carotid-cavernous fistula (CC fistula) which should be treated with high-flow bypass with trapping of the aneurysm. We also discuss and postulate the possible mechanism of aneurysm thrombosis after cervical ICA ligation.